Indoor Air Quality Investigation of Fresh Markets in Hot and Humid Climates: A Case Study in Thailand - Jirasuwanpong, Patchareepon; Yimprayoon, Chanikarn (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The issue of poor air quality in fresh market facilities poses a public health threat, particularly in association with the food supply chain. This study assessed the indoor air quality (IAQ) of various food retailers and aimed to (a) identify IAQ problems, (b) investigate the source of indoor air contamination in the fresh market, and (c) recommend better design practices for IAQ in fresh markets. The IAQ of 33 food retailers in four fresh markets in Bangkok, Thailand, was measured for ten parameters: temperature (T), relative humidity (RH), air velocity, particle matter (PM2.5, PM10), carbon dioxide (CO2), ozone (O3), formaldehyde (HCHO), total volatile organic compounds (TVOC), and bioaerosols. The result found mean values of IAQ parameters in 33 food retailers that exceeded the threshold limit values (TLVs) of the SOOK, Thailand’s well-being building standards, were PM2.5 of 30 μg/m3, HCHO of 124 μg/m3, and TVOC of 733 μg/m3. The retail stall provides fresh food products that produce wastewater from product displays and preparation, which had the highest averages of RH and bioaerosols, with RH of 66.4% and bioaerosols of 1,346 CFU/m3. The retail facilities with cooking activities, such as open kitchen restaurants, noodle restaurants, and cafés, had high averages, with PM2.5 of 51 μg/m3, HCHO of 216 μg/m3, TVOC of 922 μg/m3, and bioaerosols of 1,154 μg/m3. The stall provides dry food products with an average TVOC of 986 μg/m3, exceeding TLVs. A zoning-based approach was proposed as a design guideline to improve IAQ in fresh markets. Fresh food (FF), Dry Food (DF), and Cooking Food (CF) zoning should be carefully designed to lower the risk of cross-contamination.